The added value of Web Listening Analysis to understand communication needs regarding HIV, AIDS, and STDs in Italy - Valli, Rudi; Colucci, Anna; Gallo, Pietro; Santolini, Giulia; Belasio, Emanuele Fanales; Schwarz, Matteo; Dalla Torre, Rosa; D'Agostini, Anna; Bongiovanni, Andrea; d'Ari, Alfredo; Furiozzi, Francesca; Mirabile, Marco; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Institutional communication on human immunodeficiency virus, acquired immunodeficiency syndrome, and sexually transmitted diseases requires the knowledge of people’s information needs and tools mainly used for information on health issues. To this goal, a web listening analysis was conducted by Istituto Superiore di Sanità jointly with the Ministry of Health and experts in the field.Methods. Spontaneous listening on the web and on social channels, in relation to conversations referring to human immunodeficiency virus, acquired immunodeficiency syndrome or sexually transmitted diseases was recorded through an integrated Social Listening platform. A database of over 2 billion indexed documents was scanned and analyzed to extract documents containing at least one selected keyword on human immunodeficiency virus, acquired immunodeficiency syndrome, sexually transmitted diseases, published between October 1st 2021 and September 30th 2022.Results. Web conversations on sexually transmitted diseases took place mainly on Facebook, which is the source of almost half of overall mentions and of the 66% of total messages. However, Instagram and TikTok were the sources where most users interacted. In the sexually transmitted infections corpus of documents, the mostly used terms on the web were human immunodeficiency virus and acquired immunodeficiency syndrome. People living with the human immunodeficiency virus expose themselves very scarcely on the public web places. In the public sphere, human immunodeficiency virus and acquired immunodeficiency syndrome are faced impersonally, with opinion based on theoretical knowledge.Conclusions. Data analysis shows how the perception and discussions on human immunodeficiency virus and acquired immunodeficiency syndrome are different among the general population compared to what occurs among people living with human immunodeficiency virus disease. For the general population, the recurring elements of the analysis are seasonality, attention to news events, knowledge of human immunodeficiency virus and acquired immunodeficiency syndrome linked to the past. People living with acquired immunodeficiency syndrome do not expose themselves publicly on thr web, using more protected web places; consequently, stigma is certainly present.